Store Hygiene Check Application - Abdul Aziz, Siti Nur Aina Nisa; Saringat, Mohd Zainuri (Applied Information Technology And Computer Science, 2022)
Application of Pemeriksaan Tahap Kebersihan Gerai is an application developed to perform stall hygiene inspection work. The cleanliness of the stalls is done manually by recording the data through the forms brought to each stall. The problems faced by the Ministry of Health Malaysia is that if the forms are lost, torn or exposed to water spills it is very likely that staff will have to repeat the process. Looking at the weaknesses faced by the Ministry of Health Malaysia, then the Application of Pemeriksaan Tahap Kebersihan Gerai was developed. This application facilitates the Ministry of Health Malaysia with no need to bring necessary forms when conducting an inspection. Application development uses Dreamweaver Software, Android Studio Software and Php My admin and also uses Php C++ language as encoding and apk file. There are three users for the Application of Pemeriksaan Tahap Kebersihan Gerai, namely health officers as administrators and for users are stallers and customers. The application provides update modules for health officers, checking modules for stallholders, checking modules for the public and complaints modules for public. In addition, the application will also store all stall details, hygiene status and public complaints. It is hoped that this application is successfully developed and can help the Ministry of Health Malaysia.